2014
DOI: 10.1111/apps.12025
|View full text |Cite
|
Sign up to set email alerts
|

Narcissism and Counterproductive Work Behavior (CWB): Meta‐Analysis and Consideration of Collectivist Culture, Big Five Personality, and Narcissism's Facet Structure

Abstract: A recent review of the relationship between narcissism and CWB reported two key results: (a) narcissism is the dominant predictor of CWB among the dark triad personality traits, and (b) the narcissism–CWB relationship is moderated by ingroup collectivist culture (k = 9; N = 2,708; O'Boyle, Forsyth, Banks, & McDaniel, 2012). The current work seeks to enhance understanding of the narcissism–CWB relationship in five ways. First, we update O'Boyle et al.'s (2012) meta‐analysis to include over 50 per cent more data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
188
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(202 citation statements)
references
References 67 publications
8
188
2
4
Order By: Relevance
“…It is also probably beneficial that employers hire individuals who possess self-control because they tend to manage or regulate well their negative emotional reactions when encountering less than ideal situations. Even though there has been increasing interest in and progress on the effect of dispositional factors on employee behavior (Linton and Power, 2013;Michel and Bowling, 2013;Grijalva and Newman, 2015), many questions have yet to be answered, as indicated in the argument on the status of studies with respect to personality in personnel recruitment (Morgeson et al, 2007;Ones et al, 2007;Tett and Christiansen, 2007). Additionally, providing training to employees in emotion regulation when under stress may be useful.…”
Section: Discussionmentioning
confidence: 99%
“…It is also probably beneficial that employers hire individuals who possess self-control because they tend to manage or regulate well their negative emotional reactions when encountering less than ideal situations. Even though there has been increasing interest in and progress on the effect of dispositional factors on employee behavior (Linton and Power, 2013;Michel and Bowling, 2013;Grijalva and Newman, 2015), many questions have yet to be answered, as indicated in the argument on the status of studies with respect to personality in personnel recruitment (Morgeson et al, 2007;Ones et al, 2007;Tett and Christiansen, 2007). Additionally, providing training to employees in emotion regulation when under stress may be useful.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other research [16], employees may engage in CWB as a way to regulator their emotions and cope with work stressors. In a recent study [17], narcissism, a facet of the Big Five personality traits, has shown to be the dominant predictor of CWB after controlling for the other facets of personality.…”
Section: Explanation Of Counterproductive Work Behavior (Cwb)mentioning
confidence: 97%
“…Grijalva & Newman, 2015;O'Boyle et al, 2012). For example, in two studies, a meta-analysis and an international primary data collection, Grijalva and Newman examined the relationship between narcissism and counterproductive workplace behaviours.…”
Section: The Dark Triadmentioning
confidence: 99%
“…Building on the existing literature demonstrating links between the Dark Triad traits and CWBs (Grijalva & Newman, 2015;O'Boyle et al, 2012), and extending examination of personality and cyberloafing (e.g. Jia et al, 2013) to the Dark Triad traits, the current study presented a model to be evaluated using path analysis.…”
Section: The Current Researchmentioning
confidence: 99%
See 1 more Smart Citation